Designing a magazine - Video Education Australasia; Image Link (Bendigo, Vic. : [Video Education Australasia, 1994)
Examines the design processes used by two magazine publishers - one uses relatively simple techniques, while the other employs a high technology approach. Aspects covered include readership, production, typestyle, page layout, use of technology
Title from title screen
Script, camera & edit, Philip Ashton
Narration: Mike Lester
DVD format
Keywords: Magazine design; Publishers and publishing -- Australia; Periodicals -- Publishing -- Australia